Effect of Store Design on Perceived Crowding and Impulse Buying Behavior - Gogoi, Bidyut Jyoti (International Review of Management and Marketing, 2017)
Retailing has undergone tremendous changes in the present business environment. One reason being the increase in business of the online retailers. Customers now have a choice and preference to choose the channel of their choice. The profit margins of several retailers have gone down due to this stiff competition. To stay tuned to the changing business environment retailers need to develop strategies to increase footfalls and increase their loyal customer base. To have a loyal customer base retailers have to focus on increasing the level of shopper satisfaction. The more the shopper satisfaction, the more will be the tendency to purchase a product or service. There are several parameters associated with shopper satisfaction in a retail environment. One such parameter is the store design. In this paper, the researcher wants to find out the role of store design and its overall impact on increasing the impulse purchase behavior. The researcher uses perceived crowding as the influencer of emotional behavior of the customer. Perceived crowding is a combination of human crowding and spatial crowding. The emotional behavior generated are arousal, pleasure and dominance. The emotional behavior generated due to perceived crowding may have an impact on the shopper satisfaction level. The satisfaction level of the shoppers may in turn trigger the impulsive behavior of the customer. Keywords: Store Design, Human Crowding, Spatial Crowding, Arousal, Pleasure, Dominance, Shopper Satisfaction, Impulse Buying. JEL Classifications: M300, M310